Guilt is effectively induced by a written auto-biographical essay but not reduced by experimental pain - Schär, Selina; Vehlen, Antonia; Ebneter, Julia; Schicktanz, Nathalie; de Quervain, Dominique J. F.; Wittmann, Lutz; Götzmann, Lutz; grosse Holtforth, Martin; Protic, Sonja; Wettstein, Alexander; Egloff, Niklaus; Streitberger, Konrad; et al. (Frontiers in Behavioral Neuroscience, 2022)
Introduction: The aim of the present study was (1) to validate the method of guilt-induction by means of a written auto-biographical essay and (2) to test the moral masochism hypothesis holding that bodily pain is apt to alleviate the mental burden of guilt. This concept received support from both empirical research and clinical observation. Methods: Following guilt induction a suprathreshold pain-stimulus was administered in a cross-over design in two groups of healthy participants (heat-pain vs warmth, N = 59; cold-pressure-pain vs lukewarm water (CPT), N = 43). A visual analogue scale (VAS) guilt rating immediately after pain stimulation served as primary outcome. In a third control group (N = 39) the heat-pain experiment was performed after induction of a neutral emotional state. Results: A consistently strong overall effect of guilt-induction (heat-pain: p<.001, effect size r = .71; CPT-pain p<.001, r = .67) was found when compared to the control-condition (p =.25, r = .08). As expected, heat- and cold-pressure-stimuli were highly painful in all groups (p<.0001, r = .89). However, previous research supporting the moral-masochism hypothesis was not replicated. Conclusion: Although guilt-induction was highly effective on both test-days no impact of pain on behavioral guilt-ratings in healthy individuals could be identified. This result questions previous experimental work on the impact of pain on moral emotions.